KNOWLEDGE, ATTITUDE, AND BEHAVIOR TOWARD SMOKING AMONG MEDICAL STUDENTS IN UNIVERSITAS SUMATERA UTARA - Ivan Kendrich; Bintang Yinke Magdalena Sinaga (Universitas Airlangga, 2023)
Introduction: Tobacco consumption is one of the important contributing factors of non-infectious mortality in Indonesia. Factors causing young people to smoke include personality, parents, and colleagues. Medical students should have good knowledge about tobacco, an attitude that supports smoking avoidance and supports smoking cessation, and be role models for society by not smoking. The aim of this study is to determine about knowledge, attitude toward smoking habit, and smoking behavior among the medical students of Universitas Sumatera Utara. Method: This is a descriptive-analytical study with cross–sectional approach, conducted at Medical Faculty of Universitas Sumatera Utara (USU) from March to December 2020. Participants are 100 medical students chosen randomly using stratified random sampling. Data are collected directly from the questionnaire in the form of Google Form sent to participants. Bivariate analysis was done using Chi-Square and Fisher’s exact test. Result: shows the prevalence of smoking is 16%. For knowledge, 75% of respondent’s knowledge about tobacco is average, 22% respondents have good knowledge, and 3% respondents have poor knowledge. Attitudes toward tobacco avoidance are positive in 63% respondents and negative in 37% respondents. Smoking behavior of 37.5% smokers is high, 31.25% average, and 31.25% low. Bivariate analysis finds significant correlation between smoking status and gender, smoking peer, and attitude. Conclusion: majority of USU medical students have average knowledge about tobacco, positive attitude toward smoking avoidance, and high smoking behavior. Significant correlation found indicates the need to raise awareness of smoking hazard and effort in ceasing smoking behavior among medical students.